Shonari ergonomic pen / Amirrah Syairah Abd Ramli … [et al.] - Abd Ramli, Amirrah Syairah; Abu Bakar, Nuraina Nourin; Ishar, Nur Syazwina Izzati; Abdul Halim Ng, Siti Humairah; Jamaluddin, Nurshuhadatul Maira; Idrus, Syukurriah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Shonari Enterprise aims to supply stationery that will assist people with their daily activities effectively. We also produce our own brand which is “Shonari Ergonomic Pen” as our main product. The product comes in a long, balanced, light, and durable pen with consistent ink flow. Our main considerations are to produce a pen that can be physically comfortable to grip and does not require any excessive amount of pressure and tension when writing. Plus, the ink flow is a lifetime ink where an ink refill is not required. Therefore, we will be using rollerball pen ink that consists of water-based ink and gel ink. The reason why we choose this ink is because water-based liquid ink is thinner and has a lower viscosity compared to the oil-based ink contained in ballpoint pen ink. It helps to make it easier for people to do their work as working for a long hour can affect physical health. The well-padded and squishy pen grip that consists of rubber and silicone also helps to relieve any finger discomfort during a long writing session. Therefore, the idea of ergonomic pen is our main priority to design our product with the intention to bring the sense of comfort and minimize the risk of pain or strain around the wrist when writing. Moreover, the pen also comes with elegant Japanese elements as the decoration to make it more unique and presentable than any other pens that have existed in the market. Hence, Shonari Enterprise aims to determine the suitable equipment needed by the public in order to fulfil the users' satisfaction, especially in their writing experience. The potential for commercialization, where we will mainly focus on academic related person using the electronic and digital advertising since it will be easier to reach their attention with our product.